The Application of Chitosan Toward The Vegetative Growth of Candlenut (Reutealis Trisperma (Blanco) Airy Shaw) - Ellen Rosyelina Sasmita; Darban Haryanto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2016)
Candlenut is an important plant which has the potential to produce biofuels. Therefore, it is necessary to create a technological innovation in the cultivation of this plant in order to obtain a good vegetative growth. Thus, the generative growth become well and the plant become productive by giving chitosan, an organic fertilizer made from natural ingredients derived from shrimp shells which is processed by radiation technology to produce useful agriculture products. The aim of this research was to determine the interactions between method and frequency of Chitosan application. To factors Randomized Block Design was used as methods in this research. The first factor was Application methods of Chitosan (Pouring around near the roots, Spray to the leaves, and spray onto the stem ). The second factor was Frequency of chitosan application ( three, four and five times). As a comparation was without chitosan treatment. The result showed that there was no interaction between the treatment method and the frequency of chitosan distribution towards the vegetative growth of Reutealis trisperma (Blanco). When chitosan was sprayed onto the leaves, it gives better effect than pouring around near the roots and sprayed onto the stem. The frequency of chitosan application for three times was the best one. Plants that were treated with chitosan have better vegetative growth than those without chitosan treatment.Keywords: Candlenut, chitosan, vegetative growth